Pengaruh Gaya Kepemimpinan Lingkungan Kerja Dan Kompensasi Terhadap Kinerja Karyawan Cafe Di Makassar - Nur, Richard Muchlas; Mas’ud, Masdar; Selong, Abbas (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study is to analyze the influence of leadership style, work environment, and compensation on employee performance at cafes in Makassar, and to determine which of these variables has the most dominant effect on employee performance. This research was conducted at several cafes located in the city of Makassar. The population consisted of 4,800 actively registered cafe employees across 807 cafes. Using Slovin's formula, a total sample of 98 respondents was obtained. Data analysis employed descriptive statistics to explain research data, while quantitative analysis used Multiple Linear Regression as the analytical tool.The results show that leadership style, work environment, and compensation simultaneously have a positive and significant effect on the performance of cafe employees in Makassar. However, partially, leadership style has a negative and significant effect, indicating a mismatch between the leadership style applied and the expectations of employees. In contrast, work environment and compensation have a positive and significant effect, with the work environment being the most dominant variable. This finding emphasizes that the quality of workplace atmosphere, interpersonal relationships, physical comfort, and psychological aspects significantly contribute to improving performance, particularly in the service industry such as cafes, which rely heavily on direct interaction and a young workforce.   Keywords: Leadership Style, Work Environment, Compensation, and Employee Performance